The Global Coffee Industry: Legacy of Exploitation and Paths to Reform - Chan, Kwun Leung (International Journal of Global Economics and Management, 2024)
The global coffee industry is a product of socio-economic factors and colonial aspirations that have shaped it over centuries. Historically, coffee cultivation originated from plantations established by European colonial governments primarily in Africa and Latin America, often exploiting local labor to minimize costs and maximize profits. This legacy of exploitation has persisted, contributing to systemic inequities and power dynamics within coffee-producing countries. This paper aims to explore prevailing post-colonial ideologies and exploitative practices in the coffee industry and compares success stories from regions that have improved farmer welfare and labor conditions. A multi-case study approach is employed to contrast regions with high levels of labor exploitation in coffee plantations with those exhibiting more equitable labor practices. Findings reveal that coffee farmers in areas such as Latin America and Africa often face poverty, low wages, and harsh working conditions, while models like that in Yunnan, China, demonstrate significant improvements in farmers’ lives through government support, fair trade practices, and cooperative production. The paper discusses the underlying causes of these disparities and proposes strategies for reforming the global coffee industry, including government intervention, establishing cooperatives, and implementing fair trade certifications.